Technology based Business Incubator As An Effort to Increase Entrepreneurship in Higher Education - Sadeli; Joko Nur Utomo, Hastho; Fathi Rauf, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
Many new entrepreneurs have a crisis in managing their business, especially in the technology sector. More than 90% of startups are failing. More entrepreneurs are owned by a country will improve the economy and welfare. Higher education as a research institute can commercialize the results of research and help new technology entrepreneurs grow their business through university business incubator. University business incubator can help them through several services, such as skill development service, seed capital, co-working space and network. University business incubator is expected to find and nurture new technology entrepreneurs within the university.